Secretoneurin A Directly Regulates the Proteome of Goldfish Radial Glial Cells In Vitro - Da Fonte, Dillon F.; Martyniuk, Chris J.; Xing, Lei; Trudeau, Vance L. (Frontiers in Endocrinology, 2018)
Radial glial cells (RGCs) are the main macroglia in the teleost brain and have established roles in neurogenesis and neurosteroidogenesis. They are the only brain cell type expressing aromatase B (cyp19a1b), the enzyme that synthesizes estrogens from androgen precursors. Our previous investigations demonstrated that dopamine stimulates cyp19a1b expression in goldfish RGCs while secretoneurin A (SNa) inhibits expression of this gene. To further explore the regulation of RGC functions, we determinde the range of proteins and cellular processes responsive to SNa treatments in RGCs. Primary cultures of RGCs were treated (24 h) with 10, 100, or 1000 nM SNa. Using iTRAQ and a hybrid quadrupole Obritrap Mass Spectrometry system, a total of 1,363 unique proteins were identified in RGCs and 609 proteins were significantly regulated by SNa at one or more concentrations. Proteins that showed differential expression with all three concentrations of SNa included H1 histone, glutamyl-prolyl-tRNA synthetase, Rho GDP dissociation inhibitor γ, vimentin A2, and small nuclear ribonucleoprotein-associated protein. Subnetwork enrichment analysis of differentially regulated proteins revealed that processes such as actin organization, cytoskeleton organization and biogenesis, apoptosis, mRNA processing, RNA splicing, translation, cell growth and proliferation are regulated by SNa. Moreover, the low concentration of SNa increased the abundance of proteins involved in cell growth, proliferation, and migration whereas higher concentrations of SNa appeared to down-regulate proteins involved in these processes, indicating a dose-dependent proteomic response. When cells are treated with 1000 nM SNa, proteins linked to diseases of the CNS (brain injuries, Alzheimer disease, Parkinson’s disease, cerebral infraction, brain ischemia) were also differentially regulated. These data implicate SNa in the control of cell proliferation and neurogenesis.